1989
DOI: 10.1073/pnas.86.11.3982
|View full text |Cite
|
Sign up to set email alerts
|

Incision by UvrABC excinuclease is a step in the path to mutagenesis by psoralen crosslinks in Escherichia coli.

Abstract: ABSTRACT4,5',8-Trimethylpsoralen (psoralen) plus near UV light produces interstrand crosslinks and monoadducts in DNA, both ofwhich are mutagenic. InEscherichia coil, crosslinks are incised by UvrABC excinuclease, an event that can lead to homologous recombination and repair. To determine whether UvrABC incision of crosslinks is a step in the path to mutagenesis as well as repair, the effect of DNA homologous to a target gene on a plasmid was determined. pSV2-gpt DNA was treated with psoralen and transformed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 49 publications
(32 reference statements)
3
24
0
Order By: Relevance
“…RPA binds to triplexes with high affinity, with or without XPA, whereas XPA binds only in conjunction with RPA, but contributes to specificity by selectively diminishing nonspecific binding and͞or aggregation of RPA to undamaged DNA. Psoralen monoadducts and crosslinks are, at least in part, recognized and repaired by NER in human cells (39)(40)(41)(42)(43)(44)(45)(46). Psoralen monoadducts are somewhat helix-stabilizing, whereas crosslinks are helix-destabilizing (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…RPA binds to triplexes with high affinity, with or without XPA, whereas XPA binds only in conjunction with RPA, but contributes to specificity by selectively diminishing nonspecific binding and͞or aggregation of RPA to undamaged DNA. Psoralen monoadducts and crosslinks are, at least in part, recognized and repaired by NER in human cells (39)(40)(41)(42)(43)(44)(45)(46). Psoralen monoadducts are somewhat helix-stabilizing, whereas crosslinks are helix-destabilizing (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…The ntn jt5 allele was of recessive inheritance and fully penetrant. If TMP mutagenesis induces deletions in the zebrafish genome as in E. coli and C. elegans (Sladek et al, 1989;Yandell et al, 1994;Liu et al, 1999), it would be possible to directly clone deleted DNA segments by subtraction between pooled wild-type and mutant genomes. Alternatively, such whole-genome subtraction may allow us to obtain DNA segments tightly linked to the ntn locus if there were enough RFLPs in the AB strain genome.…”
Section: Resultsmentioning
confidence: 99%
“…TMP, in combination with UV irradiation, forms interstrand crosslinks with DNA double helices and frequently results in deletions, possibly via incomplete nucleotide excision and recombination repair in E. coli and C. elegans (Cimino et al, 1985;Sladek et al, 1989;Yandell et al, 1994). Subtraction of the mutant genome from the wild-type genome should yield deleted genes or tightly linked RFLP markers.…”
Section: Tmp Mutagenesis and Rda Cloningmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in Escherichia coli have shown that it causes both single-base changes and deletions (Piette et al 1985;Sladek et al 1989). C. elegans researchers became interested in the potential of ultraviolet trimethylpsoralen (UV/TMP) to generate deletions in worms after the first deletions in this organism were isolated using this mutagen (Yandell et al 1994).…”
mentioning
confidence: 99%